A High Salt‐Tolerant Thermoactive Esterase from Golden Grey Mullet: Purification, Characterization and Kinetic Properties. Issue 3 (17th April 2015) - Smichi, Nabil; Fendri, Ahmed; Gargouri, Youssef; Miled, Nabil
Abstract An esterase was purified from the golden grey mullet viscera using successively a Sephacryl S‐100 gel filtration, an anion‐exchange chromatography and a high‐performance liquid chromatography filtration column. The pure esterase (GmDE) is a monomer that has a molecular mass of about 55 kDa, as determined by SDS‐PAGE analysis. The purified enzyme displayed a specific activity of 100 U/mg on short‐chain triacylglycerols at a temperature of 50C. GmDE is therefore a thermoactive enzyme as compared to other fish lipolytic enzymes that have been studied so far. No significant lipolytic activity was noticed when long‐chain triacylglycerol (olive oil) was used as a substrate. It is worth noting that the pure esterase was active in the presence of salt concentrations as high as 0.8 M. The GmDE N‐terminal amino acid sequence showed no similarities with that of other known fish esterases. Altogether, these results suggest that the GmDE is a member of a new group of digestive esterases belonging to vertebrates. Practical Applications Characterization of an esterase from low‐value fish viscera and the use of digestive enzyme may add value to this discarded species. Furthermore, the activity and stability at alkaline pH may also find use in laundry detergents. The thermoactivity of the purified esterase makes it a good candidate for potential application in food processing operations. Finally, the stability of the enzyme in high salt concentrations suggests that it can be used as an additive in different processes (food, cosmetic and pharmaceutical operations).